Tranexamic acid to prevent early postpartum hemorrhages - Yu.E. Dobrokhotova; L.S. Dzhokhadze (РМЖ. Мать и дитя, 2019)
Tranexamic acid to prevent early postpartum hemorrhages Yu.E. Dobrokhotova, L.S. Djokhadze Pirogov Russian National Research Medical University, Moscow, Russian Federation Obstetric hemorrhages are among three leading causes of maternal death. Early postpartum hemorrhages occurring within 24 hours after the delivery are responsible for a quarter of maternal deaths worldwide. Continuous decrease in fibrinolytic activity and hypercoagulation occur during pregnancy. These changes are clearly adaptive. They aim to prevent physiological hemorrhage during the delivery. The paper reviews the most common causes and risk factors for postpartum hemorrhages. Modalities for the treatment of postpartum hemorrhages are discussed. In high-risk patients, preventive administration of tranexamic acid (TXA) is recommended. TXA, an antifibrinolytic agent, provides local and systemic hemostasis resulted from increased fibrinolysis. The paper addresses current data on TXA clinical use. TXA reduces maternal death rate in women with early postpartum hemorrhages regardless of delivery methods and without increased embolism risk. Some authors discuss potential routine use of TXA to prevent increased hemorrhage during cesarean section that is of great importance in high-risk groups. Key words: postpartum hemorrhage, obstetric hemorrhage, early postpartum hemorrhage, prevention of hemorrhages, hemostasis, fibrinogen, tranexamic acid, Tranexam. For citation: Dobrokhotova Yu.E., Djokhadze L.S. Tranexamic acid to prevent early postpartum hemorrhages. Russian Journal of Woman and Child Health. 2019;2(1):34–38.